The Bible expository commentary ; vol. 2 - Wiersbe, Warren W. (Wheaton, IL Victor, 1989)
Contents : v.2 : Ephesians - Revelation.
An exposition of the New Testament comprising the entire "Be" series.
Keywords: Bible. N.T. -- commentaries